Pengaruh Sikap Iklan PSBB terhadap Niat untuk Melakukan Social Distancing Di Masa Pandemi Covid-19 - Lina, Lina (Catholic University Musi Charitas, 2021)
This research describes how Advertising Response Modelling (ARM) provides a framework to measure advertising performance by integrating several multiple measures used in copy research. The author reports the study examining how social distancing policy advertising can effect of three variables: attitude toward ads, attitude toward brand, and social distancing intention. The aims of this research were to measure the influence of cognitive response and attitude toward social distancing intention in advertising and to analyze consumer’s information processing route of an ad. Survey design research was prepared in this study. The participants in this research are consumers who social distancing intention. There are 138 participants in this research. Those participants were exposed an advertisement of social distancing policy. Then, those participants filled out the self-administered and the structure questionaire. By using ARM and One way ANOVA analysis, this research shows that advertising has influenced positively thparticipants. However, there are not significantly diffrerent between men and women participants to response the advertising.